Enhancing Food Safety: Adapting to Microbial Responses Under Diverse Environmental Stressors - Imran Mohammad; Mohammed Sarosh Khan; Mohammad Rizwan Ansari; Mohammad Azhar Kamal; Mohammad Nadeem Bari; Mohammad Anwar (Trends in Ecological and Indoor Environmental Engineering)
Background: Microbial adaptation is a fundamental process by which microorganisms dynamically adjust to changes in their environment. Microbial adaptation includes both short-term and long-term mechanisms that enable microorganisms to survive and thrive in changing environmental conditions. Microbial adaptation processes can result in evolutionary changes that provide sustainable advantages. These processes allow microbes to develop traits such as antibiotic resistance and enhanced biofilm formation, ensuring their survival and proliferation in diverse environments. Despite substantial progress, there remains a critical gap in the literature regarding a comprehensive synthesis of microbial adaptation mechanisms and their implications for enhancing food safety and ensuring the sustainable production of industrially valuable biochemicals.